Abortion Article Debate and Discussion Process in Act No. 36 Year 2019 About Health - Afriana, Wendra; Mariyah, Chusnul; Azis, Harry Azhar (Universitas Brawijaya, 2019)
This article examines the process of discussing the health bill specifically relating to abortion. The pros and cons of the substance of abortion gave birth to two factions, namely pro choice and pro life. The pro life faction considers the discussion on abortion should not be submitted in the ruling. Those belong to this faction include the NGO National Movement for life, Pro life Indonesia as well as a number a mps from the PDS party in the Commission IX of the House of Representative. In opposition, the pro choice group, who support the abortion article to be included in the Bill, includes NGO Yayasan Kesehatan Erempuan, Perkumpulan Keluarga Berencana Indonesia and the majority MPs within the Commission IX from PDIP, Golkar, Demokrat, PKS, PPP, PKB, BPD, and PAN. MPs from PBR accepts the abortions article with a condition that rulings on rape victims should not be included. There are three ideological groupings based on religion, feminism, and secularism. The decision making process on the substance of the material was held privately through the lobby forum because a meeting failed to reach a settlement or approved. That the two factions finally reach on compromise agreement through lobby forum pursued by factions in order to accelerate the decision making.